A goal programming approach for the problems analyzed using the method of least squares - Ahmad, Maizah Hura (Universiti Teknologi Malaysia, 2004)
Goal programming (GP) is one of the most promising techniques for multiple objective decision analysis. Goal programming is a powerful tool which draws upon the highly developed and tested technique of linear programming, but provides a simultaneous solutions between variables, particularly for the purpose of understanding how one variable depend on one or more other variables. However, one of the main problems is that the method of least squares is biased by extreme cases. This study proposes goal programming as an alternative to analyze such problems. The analysis were done by using QM for Windows and MINITAB software package.